1978
DOI: 10.1210/jcem-47-5-974
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Levels of Gonadotropins, Prolactin, Thyroxine, and Adrenal and Gonadal Steroids in Obese Prepubertal Girls*

Abstract: Plasma levels of gonadotropins, PRL, T4, and adrenal and gonadal steroids were measured in two groups of 7- to 9-yr-old and 10- to 11-yr-old obese prepubertal girls, and were compared to those found in groups of nonobese girls of the same age. The data found in normal weight subjects confirm the data reported in the literature, showing a significant rise between the 7- to 9- and 10- to 11-yr groups, of FSH, pregnenolone, dehydroepiandrosterone, testosterone, and estradiol plasma levels, while LH, PRL, T4, cort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0
4

Year Published

1981
1981
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(34 citation statements)
references
References 0 publications
2
28
0
4
Order By: Relevance
“…Few previous investigations have examined associations between adiposity and sex hormone concentrations in girls, and most have been small cross-sectional studies with limited information on other factors, including menarcheal status, which could affect hormone levels. In an early study, obese girls had significantly higher plasma levels of DHEAS, androstenedione, and progesterone, but lower levels of estradiol, compared with nonobese girls (23). Another study found that fat mass, assessed by skinfold thicknesses, was positively associated with levels of DHEAS and non -SHBGbound testosterone, but girls in the highest WHR quartile had the lowest concentrations of total and non -SHBG-bound estradiol and testosterone (24,25).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Few previous investigations have examined associations between adiposity and sex hormone concentrations in girls, and most have been small cross-sectional studies with limited information on other factors, including menarcheal status, which could affect hormone levels. In an early study, obese girls had significantly higher plasma levels of DHEAS, androstenedione, and progesterone, but lower levels of estradiol, compared with nonobese girls (23). Another study found that fat mass, assessed by skinfold thicknesses, was positively associated with levels of DHEAS and non -SHBGbound testosterone, but girls in the highest WHR quartile had the lowest concentrations of total and non -SHBG-bound estradiol and testosterone (24,25).…”
Section: Discussionmentioning
confidence: 99%
“…Only a few studies have examined whether adiposity in childhood and adolescence is related to levels of sex hormones in girls, and the results are inconclusive (23)(24)(25)(26)(27). Previous studies have been hampered by small numbers of participants and limited information on other factors, including menarcheal status and day of the menstrual cycle, which could influence hormone levels.…”
Section: Introductionmentioning
confidence: 99%
“…Although DBMI is associated with serum leptin levels, it may also be an Effects of obesity on puberty S Shalitin and M Phillip integrated measure of the combined long-term actions of IGF-I and insulin, which have been shown to augment adrenal androgen production and the expression of steroidogenic enzymes in human adrenocortical cells. 49 Adrenal androgen levels are increased in children with obesity 50 and may therefore be responsible for their accelerated growth before puberty. 51 This assumption is supported by data pointing to a specific, dose-dependent, stimulatory activity of leptin on 17-a-hydroxylase and 17-20 lyase, both enzymes essential for the synthesis of adrenal androgens.…”
Section: Obesity and Pubertymentioning
confidence: 99%
“…10 Further, a link between body fatness and the hormonal changes that lead to the onset of menarche has been implicated. [11][12][13][14][15][16] However, the temporal direction of this relationship remains uncertain. Nonetheless, in view of the secular trend toward increasing obesity occurring in the pediatric population of the US, 17,18 it is important to examine the consequences of excess body fatness related to early menarche at the population level.…”
Section: Introductionmentioning
confidence: 99%